Carbon monoxide transmission simulation in the ambient at Vietnam National Military Training Center No.3 and infantry shooting range combines weapons testing by aermod model - Trần Tuấn Việt; Trần Ngọc Lam Tuyền; Nguyễn Thị Ngọc Phượng; Trần Hải Nam; Nguyễn Tất Thành (Journal of Military Science and Technology, 2022)
Vietnam National Military Training Center No.3 (TB3) and Infantry shooting range combines weapons testing (Thach That distric, Ha Noi) are places for military training, live-fire drills, competitions, sports festivals, testing of weapons and destruction of expired bombs. Besides generating pollution sources such as wastewater, solid waste, the operation of the training center also cause some air pollutants, one of the main products from the combustion process is carbon monoxide (CO). This study was carried out to simulate the CO spread in the air from the live-fire training at TB3 and Infantry shooting range combines weapons testing using the TAPM meteorological model system and the AERMOD air quality model. The results from the model show that the highest 1h-average CO concentration in the area around TB3 was 5,558 µg/m3, which was similar the previous monitoring results in this area. This set of parameters is applied to calculate the infantry shooting range combined with weapon testing, showing that the highest 1h-average CO concentration value was 4,762 µg/m3 at the firing line position lower than QCVN 05/2013/ BTNMT. The research data also proved that CO from live-fire training was not enough to cause air pollution around nearby residential areas.